PEREMPUAN DALAM WACANA SASTRA - Nurrahma Primiani (Jurnal Salome : Multidisipliner Keilmuan, 2025)
This study entitled “Perempuan dalam Wacana Sastra” investigates how women are represented and depicted in a literary work, such as novel and short stories, both as an author of the work and character of the stories themselves. By taking the discourse of women and literary work and patriarchal ideology, women are shown to have similar pattern of tasks and duties. By taking the discourse of combining Cixous’ approach on iterary works and Bordo’s patriarchal context, women are shown to have similar ambigous tasks and roles, both in the story plot and their social life. This article argues that women are forced to adhere to the same pattern and to two prevailing standards in social life. After analyzing the data, this article reveals the view that women's presence is consistently repressed, both in literary works and in social life.